First Branchial Cleft Malformation with Duplication of External Auditory Canal. (7th November 2013) - Parida, Pradipta Kumar; Alexander, Arun; Raja, Kalairasi; Surianarayanan, Gopalakrishnan; Ganeshan, Sivaraman
Abstract : First branchial cleft anomalies are uncommon, accounting for less than 10% of all branchial abnormalities. Their rare occurrence and varied presentation have frequently led to misdiagnosis and inadequate and inappropriate treatment of these conditions leading to repeated recurrences and secondary infection. In this paper, a case of 11-year girl with type 2 first branchial cleft defect is described. She first presented with a nonhealing ulcer of upper neck from childhood. Diagnosis had previously been missed and treated as tubercular ulcer. We confirmed the correct diagnosis by history and computerized tomography fistulogram. The lesion was completely excised with no further recurrence.